Can One Speak of Solidarity and Apology in Guaman Poma’s Narrative about the Indians in the “Good government”? - Morales, Mónica (2020)
In the middle of discursive struggles, Guaman Poma spoke about the Indigenous people of the New World and informed the king about the impact of colonization in the Andes. ¿What could this author do totransmit to the king an accurate representation of what he described? This essay reﬂects on the problems of representation when dealing with “others”, a crucial issue for Guaman Poma’s political and ethical goals.In this context, discourses of subalternity and human rights converged in a discussion about the issues of such discourses and their validity. This article suggests that there are areas pending of study about the intellectual production, justice and identity politics that are activated when Guaman Poma builds  representation of Andean people.